PENGARUH TINGKAT PARTISIPASI ANGKATAN KERJA, INDEKS PEMBANGUNAN MANUSIA DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP TINGKAT KEMISKINAN - Widyawati, Retno Febriyastuti; Suma Pratama, Fani; Fransina Diana Talakua, Jeane; Nainggolan, Elisabeth (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2025)
Poverty remains a challenge for regional development, including in Batang Regency. This study aims to analyze the influence of the Labor Force Participation Rate (LFPR), the Human Development Index (HDI), and the Gross Regional Domestic Product (GRDP) on the poverty rate in Batang Regency from 2007 to 2024. The research method employed was a quantitative approach, utilizing secondary data obtained from the Central Statistics Agency (BPS). The results indicate that the LFPR has a positive but statistically insignificant effect on poverty, suggesting that the availability of productive employment has not fully kept pace with the increase in labor force participation. The HDI has a negative and insignificant effect on poverty, suggesting that improvements in education, health, and livings standard have not been evenly distributed across all levels of society. Meanwhile, the GRDP rate shows a negative and significant effect, indicating that economic growth can significantly contribute to poverty reduction. Keywords: LFPR, IPM, GRDP Rate, Poverty